THE NATURE OF EDUCATION IN HINDI NOVELS: IDEOLOGICAL, CULTURAL, AND SOCIAL PERSPECTIVES WITH SPECIAL REFERENCE TO THE NOVELS OF PREMCHAND AND SHRILAL SHUKLA - Nandkishor; Verma, Gulab Singh (International Journal of Research -GRANTHAALAYAH, 2026)
This research paper presents an analysis of the evolving nature of education in Hindi novels from ideological, cultural, and social perspectives. Education is not merely a medium for acquiring knowledge; it serves as the foundation for social change and nation-building. This study centers on selected novels by two prominent novelists—Premchand (a doyen of the realist tradition) and Shrilal Shukla (a towering figure of satirical realism). The diverse dimensions of education have been examined in depth within Premchand’s *Sevasadan*, *Karmabhumi*, and *Godan*, as well as Shrilal Shukla’s *Sooni Ghati Ka Suraj* and *Raag Darbari*. The study concludes that while in Premchand’s works, education emerges as a medium for combating social evils and fostering self-awakening, Shrilal Shukla employs satire to expose the disintegration of education’s idealistic essence due to corruption within educational institutions and the pursuit of political self-interest.